A catalyst with self-repairing performance and a preparation method and application thereof
Patent Information
- Application Number
- CN202410717246.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-06-04
AI Technical Summary
上述过程将会产生大量异丁酸酐裂解尾气,尾气排放量大,毒性强,成分复杂,包含多种有机污染物(羧酸、酯、酸酐、醛、酮、烷烃、烯烃等)、无机污染物(氮氧化物、硫氧化物)和水蒸气
[0053]该催化剂具有钙钛矿结构,性质稳定,有较好的水热稳定性,耐高温、耐酸碱,用于催化氧化处理异丁酸酐裂解尾气,可展现出优异的效果。
Smart Images

Figure CN118634831B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of environmental functional materials technology, and in particular to a catalyst with self-healing properties, its preparation method, and its application. Background Technology
[0002] 2,2,4,4-Tetramethyl-1,3-cyclobutanedione (TMCB) is an important chemical material used in the production of novel polyester monomers. Currently, its main industrial synthesis method involves the cracking of isobutyric anhydride to prepare dimethyl ketene (DMK), followed by the dimerization of DMK to obtain TMCB. This process includes cracking, condensation, absorption, and dimerization reactions. This process generates a large volume of isobutyric anhydride cracking tail gas, which is highly toxic, complex in composition, and contains various organic pollutants (carboxylic acids, esters, anhydrides, aldehydes, ketones, alkanes, alkenes, etc.), inorganic pollutants (nitrogen oxides, sulfur oxides), and water vapor. Traditional catalysts have poor hydrothermal stability, resulting in poor performance and short lifespans in treating isobutyric anhydride cracking tail gas. Analysis of their deactivation causes indicates that the main issues are catalyst carbon deposition and agglomeration of the active catalyst components. While noble metal catalysts offer good performance, they are expensive, and long-term use also presents the problem of agglomeration of the noble metal active components. Summary of the Invention
[0003] In view of this, one objective of this application is to provide a catalyst with self-healing properties, which has a perovskite structure, stable properties, good hydrothermal stability, high temperature resistance, and acid and alkali resistance, and can exhibit excellent performance when used for catalytic oxidation treatment of isobutyric anhydride cracking tail gas.
[0004] Another objective of this application is to provide a method for preparing a catalyst with self-healing properties.
[0005] Another objective of this application relates to the application of catalysts with self-healing properties.
[0006] Another objective of this application is to provide a method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas.
[0007] To achieve the above objectives, a first aspect of this application provides a catalyst with self-healing properties, the catalyst comprising at least one of the compounds represented by Formula I;
[0008] BaCo x Pb (1-x) O3 type I.
[0009] Where 0 ≤ x ≤ 0.4;
[0010] The compound represented by Formula I has a perovskite structure.
[0011] In some implementations, the value of x is between 0.2 and 0.3.
[0012] A second aspect of this application provides a method for preparing the above-mentioned catalyst with self-healing properties, comprising:
[0013] The catalyst with self-healing properties was prepared using a nano-casting method.
[0014] In some embodiments, the preparation of the self-healing catalyst using a nanocasting method includes:
[0015] The template agent and silicon source are subjected to a hydrothermal synthesis reaction, followed by a first calcination to obtain a hard template agent;
[0016] The hard template agent, the composite solution containing M source, and the additives were mixed and then subjected to rotary evaporation to obtain a precipitate;
[0017] The precipitate was dried, then calcined and washed to obtain the oxidized catalyst with self-healing properties.
[0018] The catalyst with self-healing properties in the oxidized state is subjected to a first heat treatment under a first reducing atmosphere to obtain the catalyst with self-healing properties.
[0019] In the composite solution containing source M, M is Ba and Pb, or M is Ba, Co and Pb.
[0020] In some embodiments, the template agent includes at least one of triblock copolymer P121, triblock copolymer P123, and triblock copolymer F127.
[0021] Preferably, the template agent is a mixture of triblock copolymer P121, triblock copolymer P123, and triblock copolymer F127 in a molar ratio of 1:1:1.
[0022] In some embodiments, the silicon source includes at least one of tetraethyl orthosilicate, tetramethyl orthosilicate, and tetrapropoxysilane.
[0023] Preferably, the silicon source is tetraethyl orthosilicate.
[0024] In some embodiments, the mass ratio of the template agent to the silicon source is (1-5):(50-500).
[0025] In some embodiments, the temperature of the hydrothermal synthesis reaction is 80-150°C, and the time of the hydrothermal synthesis reaction is 12-24 hours.
[0026] Preferably, the temperature of the hydrothermal synthesis reaction is 90-110℃.
[0027] In some embodiments, the temperature of the first calcination is 400-800°C, and the calcination time is 2-4 hours.
[0028] Preferably, the temperature of the first roasting is 550-700℃.
[0029] In some embodiments, in the composite solution containing source M, the molar concentration of source Ba is 10 mmol / L, the molar concentration of source Co is 0-4 mmol / L, the molar concentration of source Pb is 6-10 mmol / L, and the total molar concentration of sources Co and Pb is 10 mmol / L.
[0030] In some embodiments, the solvent in the composite solution containing source M includes, but is not limited to, water.
[0031] In some embodiments, the adjuvant includes at least one of citric acid, oxalic acid, and myristic acid.
[0032] Preferably, the additive is citric acid.
[0033] In some embodiments, the calcination temperature is 800-1100°C, and the calcination time is 3-6 hours.
[0034] Preferably, the calcination temperature is 950-1000℃ and the calcination time is 4-5 hours.
[0035] In some embodiments, the detergent used for washing includes an alkaline solution, which includes at least one of 10-40 wt% sodium hydroxide solution, 10-40 wt% potassium hydroxide solution, or a mixed solution of 10-40 wt% sodium hydroxide and potassium hydroxide.
[0036] In some embodiments, the first reducing atmosphere comprises hydrogen.
[0037] Preferably, the reducing atmosphere is a mixture of hydrogen and an inert gas, wherein the hydrogen flow rate is 5-25 mL / min and the argon flow rate is 15-75 mL / min.
[0038] In some embodiments, the temperature of the first heat treatment is 400-1000°C, and the duration of the first heat treatment is 1-6 hours.
[0039] Preferably, the temperature of the first heat treatment is 400-800℃, and the time of the first heat treatment is 2-4 hours.
[0040] In some embodiments, the mass ratio of the hard template agent, the M source, and the auxiliary agent is (1-5):(0.5-10):(0.1-0.5).
[0041] The third aspect of this application relates to the application of the self-healing catalyst as described above, or the self-healing catalyst prepared by the method described above, in exhaust gas treatment.
[0042] The fourth aspect of this application discloses a method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas, comprising:
[0043] The isobutyric anhydride cracking tail gas is treated by catalytic oxidation using a catalyst, wherein the catalyst is the self-healing catalyst as described in claim 1 or 2, or the self-healing catalyst prepared by the preparation method of the self-healing catalyst as described in any one of claims 3 to 8.
[0044] In some embodiments, the conditions for catalytic oxidation treatment of isobutyric anhydride cracking tail gas include: a reaction temperature of 250-500°C and a reaction space velocity of 4000-5000 h⁻¹. -1 The volume of oxygen used is 10-40% of the volume of isobutyric anhydride cracking tail gas.
[0045] In some embodiments, the method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas further includes:
[0046] When the catalyst is deactivated, its activity is restored through pretreatment;
[0047] The pretreatment method includes: sequentially oxidizing and reducing the deactivated catalyst;
[0048] In some embodiments, the oxidation process is carried out in an oxygen-containing atmosphere.
[0049] In some embodiments, the oxidation treatment method includes: second calcining the deactivated catalyst in an oxygen-containing atmosphere at 400-800°C for 2-4 hours.
[0050] In some embodiments, the reduction process is carried out in a second reducing atmosphere, which includes hydrogen.
[0051] In some embodiments, the reduction treatment method includes: subjecting the deactivated catalyst, which has undergone the oxidation treatment, to a second heat treatment at 400-800°C for 2-4 hours in a second reducing atmosphere.
[0052] The self-healing catalyst described in this application can bring at least the following beneficial effects:
[0053] This catalyst has a perovskite structure, is stable, has good hydrothermal stability, and is resistant to high temperatures and acids and alkalis. It exhibits excellent performance when used for the catalytic oxidation treatment of isobutyric anhydride cracking tail gas.
[0054] The method for preparing the self-healing catalyst described in this application, in addition to possessing the beneficial effects of the aforementioned self-healing catalyst, also has at least the following beneficial effects:
[0055] Through high-temperature oxidation and reduction, reversible desolvation (in a reducing atmosphere) and resolvation (in an oxidizing atmosphere) of active components can be achieved on the surface and inside the perovskite lattice. During reduction, the active components dissolve from the catalyst surface and are confined and highly dispersed on the catalyst surface (effectively inhibiting the agglomeration of noble metal elements); during oxidation, the active components resolvate into the perovskite lattice, and the carbon deposits on the catalyst surface are burned off. This method can solve the problems of carbon deposition and active component agglomeration in traditional catalytic oxidation catalysts, thereby achieving catalyst self-repair and maintaining high catalytic activity. In addition, during the reduction operation, a large number of oxygen vacancies can be generated inside and on the surface of the catalyst lattice. Oxygen vacancies are important reactive sites for catalytic reactions, thus contributing to the rapid treatment of isobutyric anhydride cracking tail gas.
[0056] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0057] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings.
[0058] in:
[0059] Figure 1 Comparison of X-ray diffraction (XRD) test results of the catalysts prepared in Examples 1-4.
[0060] Figure 2 The image shows the X-ray photoelectron spectroscopy (XPS) test pattern of the catalyst prepared in Example 1; where "counts / s" is the photoelectron count rate, "Intensity" is the relative intensity, and "Binding Energy" is the binding energy.
[0061] Figure 3 The graphs show the reaction performance evaluation of the catalysts prepared in Examples 1-4 and Comparative Examples 1-2.
[0062] Figure 4 This is a lifetime evaluation diagram of the catalyst prepared in Example 4. Detailed Implementation
[0063] The embodiments of this application are described in detail below, with examples of these embodiments illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.
[0064] In this application, the disclosure of numerical ranges includes all values throughout the range and the disclosure of further subdivisions of the range, including the endpoints and subranges given for these ranges.
[0065] Unless otherwise specified, all raw materials and equipment involved in this application are self-made through commercial means or known methods; and all methods involved are conventional methods unless otherwise specified.
[0066] <Catalysts with self-healing properties>
[0067] The catalyst with self-healing properties in this application includes at least one of the compounds represented by Formula I;
[0068] BaCo x Pb (1-x) O3 type I.
[0069] Where 0 ≤ x ≤ 0.4;
[0070] The compound shown in Formula I has a perovskite structure.
[0071] As a non-restrictive list, the values of x include, but are not limited to, 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, or 0.4.
[0072] As an optional example, x can take values from 0.2 to 0.3.
[0073] The catalyst with self-healing properties in the embodiments of this application can bring at least the following beneficial effects:
[0074] (1) The catalyst has a perovskite structure, is stable, has good hydrothermal stability, and is resistant to high temperature and acid and alkali. It can show excellent effect when used for catalytic oxidation treatment of isobutyric anhydride cracking tail gas.
[0075] (2) When the transition metal active component Co is incorporated into the perovskite lattice, the catalyst properties are more stable, and the hydrothermal stability, high temperature resistance and acid resistance are also better.
[0076] <Preparation method of catalyst with self-healing properties>
[0077] The method for preparing the self-healing catalyst of the embodiments of this application can be used to prepare the self-healing catalyst of the embodiments of this application. The method uses nanocasting to prepare the above-mentioned self-healing catalyst.
[0078] In some embodiments, a catalyst with self-healing properties is prepared using a nanocasting method, comprising the following steps:
[0079] S101. The template agent and silicon source are subjected to a hydrothermal synthesis reaction, followed by a first calcination to obtain a hard template agent.
[0080] In some embodiments, the template agent includes, but is not limited to, at least one of the following: triblock copolymer P121 (Chinese name: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer; CAS No.: 9003-11-6), triblock copolymer P123 (Chinese name: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer; CAS No.: 9003-11-6), and triblock copolymer F127 (Chinese name: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer; CAS No.: 9003-11-6).
[0081] As an alternative example, the template agent is a mixture of triblock copolymer P121, triblock copolymer P123, and triblock copolymer F127 in a molar ratio of 1:1:1.
[0082] In some embodiments, the silicon source includes, but is not limited to, at least one of tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate, tetrapropoxysilane, etc.
[0083] As an alternative example, the silicon source is tetraethyl orthosilicate.
[0084] In some embodiments, the mass ratio of template agent to silicon source is (1-5):(50-500), including but not limited to 1:100, 1:200, 1:300, 1:400, 3:100, 3:200, 3:400, 5:200, 5:400 or 5:50.
[0085] In some embodiments, the temperature of the hydrothermal synthesis reaction is 80-150°C, including but not limited to 80°C, 100°C, 120°C, 140°C or 150°C.
[0086] In some embodiments, the hydrothermal synthesis reaction takes 12-24 hours, including but not limited to 12 hours, 15 hours, 18 hours, or 21 hours.
[0087] As an alternative example, the temperature of the hydrothermal synthesis reaction is 90-110℃, including but not limited to 90℃, 100℃ or 110℃.
[0088] In some embodiments, the temperature of the first calcination is 400-800°C, including but not limited to 400°C, 500°C, 600°C, 700°C or 800°C.
[0089] In some embodiments, the first roasting time is 2-4 hours, including but not limited to 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.
[0090] As an alternative example, the temperature of the first roasting is 550-700°C, including but not limited to 550°C, 600°C or 650°C.
[0091] S102. The hard template agent obtained in step S101, the composite solution containing source M, and the additives are mixed and then subjected to rotary evaporation to obtain a precipitate; in the composite solution containing source M, M is Ba and Pb, or M is Ba, Co, and Pb.
[0092] In some embodiments, the preparation of a self-healing catalyst using nanocasting further includes the step of preparing a composite solution containing an M source. That is, the preparation of a self-healing catalyst using nanocasting further includes the step of preparing a composite solution containing a Ba source, a Co source, and a Pb source.
[0093] By way of non-limiting example, the Ba source includes, but is not limited to, at least one of Ba(CH3CO2), barium nitrate, barium chloride, etc.
[0094] In some embodiments, in the composite solution containing source M, the molar concentration of source Ba is 10 mmol / L, the molar concentration of source Co is 0-4 mmol / L, the molar concentration of source Pb is 6-10 mmol / L, and the total molar concentration of sources Co and Pb is 10 mmol / L.
[0095] By way of non-limiting example, in a composite solution containing source M, the molar concentration of source Co includes, but is not limited to, 0 mmol / L, 1 mmol / L, 2 mmol / L, 3 mmol / L, or 4 mmol / L, and the molar concentration of source Pb includes, but is not limited to, 6 mmol / L, 7 mmol / L, 8 mmol / L, 9 mmol / L, or 10 mmol / L.
[0096] In some embodiments, the solvent in the composite solution containing source M includes, but is not limited to, water.
[0097] As an alternative example, in a composite solution containing source M, the solvent is deionized water.
[0098] It should be noted that when preparing a composite solution containing source M, nitric acid or similar substances can be added dropwise to inhibit the hydrolysis of metal salts.
[0099] In some embodiments, the adjuvant includes, but is not limited to, at least one of citric acid, oxalic acid, myristic acid, etc.
[0100] As an alternative example, the adjuvant is citric acid.
[0101] In some embodiments, the mass ratio of the hard template agent, M source, and additive is (1-5):(0.5-10):(0.1-0.5), including but not limited to 5:1.25:0.5, 5:1.146:0.5, 5:0.14:0.5, 2:0.55:0.1, or 3:0.65:0.24, etc.
[0102] In some embodiments, the rotary evaporation is carried out in a rotary evaporator, and the precipitate is obtained by rotary evaporation until dry (i.e., after the solvent has evaporated and escaped).
[0103] As an optional example, the method for mixing the hard template agent obtained in step S101, the composite solution containing source M, and the additive is as follows: mix the hard template agent obtained in step S101 with the composite solution containing source M, and then add the additive.
[0104] S103. The precipitate obtained in step S102 is dried, calcined, and washed to obtain an oxidized catalyst with self-healing properties.
[0105] In some embodiments, calcination is carried out in an air atmosphere or an oxygen atmosphere.
[0106] In some embodiments, the calcination temperature is 800-1100℃, including but not limited to 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, or 1100℃. Calcination temperatures within this range produce catalysts with uniform particle size; below 800℃, the target substance, barium leadate, cannot be formed; above 1100℃, the particle size increases significantly, and the catalytic effect deteriorates.
[0107] As an alternative example, the calcination temperature is 950-1000℃.
[0108] In some embodiments, the calcination time is 3-6 hours, including but not limited to 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours or 5.5 hours.
[0109] As an alternative example, the calcination time is 4-5 hours.
[0110] In the embodiments of this application, the detergent used for washing includes concentrated alkaline solution.
[0111] As an optional example, the concentrated alkaline solution includes, but is not limited to, at least one of the following: a 10-40 wt% sodium hydroxide solution, a 10-40 wt% potassium hydroxide solution, or a 10-40 wt% mixed solution of sodium hydroxide and potassium hydroxide (with water as the solvent), such as a 15% sodium hydroxide solution or a 20% potassium hydroxide solution. It should be noted that in the 10-40 wt% mixed solution of sodium hydroxide and potassium hydroxide, the sodium hydroxide and potassium hydroxide can be mixed in any mass ratio.
[0112] As a preferred example, the detergent used for washing is an alkaline solution with a temperature of 35-45°C and a mass fraction of 30%-40% sodium hydroxide / potassium hydroxide.
[0113] In the embodiments of this application, the number of washing cycles can be one or more (more than two times).
[0114] S104. The oxidized catalyst with self-healing properties obtained in step S103 is subjected to a first heat treatment under a first reducing atmosphere to obtain a catalyst with self-healing properties.
[0115] In some implementations, the first reducing atmosphere includes hydrogen.
[0116] In other embodiments, the first reducing atmosphere further includes an inert gas, which includes, but is not limited to, at least one of argon, nitrogen, helium, etc.
[0117] As an alternative example, the first reducing atmosphere is a mixture of hydrogen and an inert gas, wherein the volume ratio of hydrogen to inert gas is (5-25):(15-75), preferably 1:3.
[0118] For example, the first reducing atmosphere is a mixture of hydrogen and inert gas, with a hydrogen flow rate of 5-25 mL / min and an argon flow rate of 15-75 mL / min.
[0119] In some embodiments, the temperature of the first heat treatment is 400-1000°C, including but not limited to 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, or 1000°C.
[0120] As an alternative example, the temperature of the first heat treatment is 400-800℃.
[0121] In some implementations, the first heat treatment time is 1-6 hours, including but not limited to 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours.
[0122] As an alternative example, the first heat treatment time is 2-4 hours.
[0123] The method for preparing the self-healing catalyst of this application, in addition to having the beneficial effects of the aforementioned self-healing catalyst, also has at least the following beneficial effects:
[0124] Through high-temperature oxidation and reduction, reversible desolvation (in a reducing atmosphere) and resolvation (in an oxidizing atmosphere) of active components can be achieved on the surface and inside the perovskite lattice. During reduction, the active components dissolve from the catalyst surface and are confined and highly dispersed on the catalyst surface (effectively inhibiting the agglomeration of noble metal elements); during oxidation, the active components resolvate into the perovskite lattice, and the carbon deposits on the catalyst surface are burned off. This method can solve the problems of carbon deposition and active component agglomeration in traditional catalytic oxidation catalysts, thereby achieving catalyst self-repair and maintaining high catalytic activity. In addition, during the reduction operation, a large number of oxygen vacancies can be generated inside and on the surface of the catalyst lattice. Oxygen vacancies are important reactive sites for catalytic reactions, thus contributing to the rapid treatment of isobutyric anhydride cracking tail gas.
[0125] Applications of catalysts with self-healing properties
[0126] The self-healing catalyst of the present application embodiments or the self-healing catalyst prepared by the preparation method of the self-healing catalyst of the present application embodiments can be widely used in tail gas treatment, wherein the tail gas includes, but is not limited to, at least one of isobutyric anhydride cracking tail gas, isobutyric acid cracking tail gas, and mixed cracking tail gas of isobutyric acid and isobutyric anhydride.
[0127] <Method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas>
[0128] The method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas according to embodiments of this application includes:
[0129] The isobutyric anhydride cracking tail gas is treated by catalytic oxidation using a catalyst. The catalyst is either the self-healing catalyst of the present application embodiment or a self-healing catalyst prepared by the preparation method of the self-healing catalyst of the present application embodiment.
[0130] In some embodiments, when isobutyric anhydride cracking tail gas is treated by catalytic oxidation with a catalyst, the flow rate of isobutyric anhydride cracking tail gas is 180-220 mL / min, including but not limited to 185 mL / min, 190 mL / min, 195 mL / min, 200 mL / min, 205 mL / min, 210 mL / min or 215 mL / min.
[0131] In some embodiments, the amount of catalyst used is 1 / 20 to 1 / 10 of the flow rate of isobutyric anhydride cracking tail gas per minute, such as 1 / 18, 1 / 15 or 1 / 12.
[0132] As an alternative example, when using a catalyst to catalytically oxidize the isobutyric anhydride cracking tail gas, if the flow rate of the isobutyric anhydride cracking tail gas is 200 mL / min, the amount of catalyst used is 10-20 mL.
[0133] In some cases, by way of non-limiting example, the isobutyric anhydride cracking tail gas includes the following components in volume fractions: CO 10-40%, nitrogen 30-40%, CO2 5-10%, isobutyric anhydride 5-10%, and isobutyric acid 5-10%.
[0134] In other cases, by way of non-limiting example, the isobutyric anhydride cracking tail gas includes the following components in volume fractions: CO 10-40%, nitrogen 30-50%, CO2 5-10%, isobutyric anhydride 5-10%, isobutyric acid 5-10%, and oxygen 5-10%.
[0135] In some other cases, by way of non-limiting example, the isobutyric anhydride cracking tail gas includes the following components in volume fractions: CO 10-40%, nitrogen 30-50%, CO2 0-10%, isobutyric anhydride 0-10%, isobutyric acid 0-10%, and oxygen 5-10%.
[0136] In some embodiments, the conditions for catalytic oxidation treatment of isobutyric anhydride cracking tail gas include: a reaction temperature of 250-500°C and a reaction space velocity of 4000-5000 h⁻¹. -1 The volume of oxygen used is 10-40% of the volume of isobutyric anhydride cracking tail gas.
[0137] By way of non-limiting example, the above reaction temperatures include, but are not limited to, 250°C, 300°C, 350°C, 400°C, 450°C, or 500°C.
[0138] By way of non-limiting example, the above reaction space velocities include, but are not limited to, 4000 h⁻¹. -1 4200h -1 4500h -1 4700h -1 or 5000h -1 wait.
[0139] By way of non-limiting example, the above-mentioned oxygen volume usage is 10%, 20%, 30% or 40% of the volume of isobutyric anhydride cracking tail gas, etc.
[0140] In some embodiments, the method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas further includes:
[0141] When the catalyst is deactivated, it is restored to activity through pretreatment to obtain a regenerated catalyst.
[0142] In some embodiments, the above pretreatment method includes: sequentially oxidizing and reducing the deactivated catalyst.
[0143] In some embodiments, the oxidation process is carried out in an oxygen-containing atmosphere.
[0144] By way of a non-limiting example, the aforementioned oxygen-containing atmosphere includes, but is not limited to, air, oxygen, etc.
[0145] In some embodiments, the oxidation treatment method includes: second calcining the deactivated catalyst in an oxygen-containing atmosphere at 400-800°C for 2-4 hours.
[0146] In some implementations, the second roasting is carried out in a muffle furnace or a tube furnace.
[0147] By way of non-limiting example, the temperature of the second roasting includes, but is not limited to, 400°C, 500°C, 600°C, 700°C, or 800°C.
[0148] As a non-limiting example, the second roasting time includes, but is not limited to, 2 hours, 3 hours, or 4 hours.
[0149] In some embodiments, the reduction process is carried out in a second reducing atmosphere, which includes hydrogen.
[0150] In other embodiments, the second reducing atmosphere further includes an inert gas, which includes, but is not limited to, at least one of argon, nitrogen, and helium.
[0151] As an alternative example, the second reducing atmosphere is a mixture of hydrogen and an inert gas, wherein the volume ratio of hydrogen to inert gas is (5-25):(15-75), preferably 1:3.
[0152] For example, the first reducing atmosphere is a mixture of hydrogen and inert gas, with a hydrogen flow rate of 5-25 mL / min and an argon flow rate of 15-75 mL / min.
[0153] In some embodiments, the reduction treatment method includes: subjecting the deactivated catalyst, which has undergone the above-mentioned oxidation treatment, to a second heat treatment at 400-800°C for 2-4 hours in a second reducing atmosphere.
[0154] By way of non-limiting example, the temperature of the second heat treatment includes, but is not limited to, 400°C, 500°C, 600°C, 700°C, or 800°C.
[0155] By way of a non-limiting example, the duration of the second heat treatment includes, but is not limited to, 2 hours, 3 hours, or 4 hours.
[0156] In some implementations, the second heat treatment is carried out in a muffle furnace or a tube furnace.
[0157] The following non-limiting embodiments further illustrate certain features of the present technology.
[0158] I. Catalyst Preparation
[0159] The concentrated nitric acid mentioned in each embodiment refers to 68 wt% nitric acid.
[0160] Example 1
[0161] The method for preparing the self-healing catalyst in this embodiment includes the following steps:
[0162] (1) Weigh equal amounts (5 mmol) of three triblock copolymers, P121, P123 and F127, using an analytical balance. Dissolve the three substances in 200 mL of 1 mol / L hydrochloric acid solution and stir in a 30 °C water bath until completely dissolved to obtain a mixture.
[0163] (2) 30 mL of tetraethyl orthosilicate (TEOS) was slowly added to the mixture obtained in step (1), and stirred at 400 r / min for 10 h in a 30 °C water bath. The resulting milky white mixture was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and placed in an oven for hydrothermal synthesis at 120 °C for 24 h. The polytetrafluoroethylene-lined hydrothermal reactor was removed, cooled to room temperature, the sample was filtered, dried at 100 °C, and then transferred to a muffle furnace and calcined at 550 °C for 4 h to obtain a hard film agent.
[0164] (3) Weigh 0.682g (1.8mmol) Pb(CH3CO2)2·3H2O, 0.510g (2mmol) Ba(CH3CO2) and 0.058g (0.2mmol) Co(NO3)26H2O, transfer them into 200mL of deionized water, and add 0.15-0.2mL (e.g., 0.2mL) of concentrated nitric acid to inhibit the hydrolysis of the metal salt and obtain a composite solution.
[0165] (4) Weigh 5g of the hard film agent obtained in step (2) and 0.5g of citric acid and add them to the composite solution obtained in step (3). After stirring and mixing, transfer the mixture to a rotary evaporator and evaporate it to dryness to obtain the precipitate.
[0166] (5) After drying the precipitate obtained in step (4), it was calcined in a muffle furnace at 950°C for 4 hours. After calcination, the sample was washed in 100 mL of 30 wt% sodium hydroxide solution at 40°C for 4 hours to obtain the oxidized catalyst (BaCo). 0.1 Pb 0.9 O3) 氧化态 .
[0167] (6) Take the (BaCo) obtained in step (5) 0.1 Pb 0.9 O3) 氧化态The catalyst was transferred to a tubular furnace and reduced at 600°C for 4 hours in a mixed gas atmosphere of 10 mL / min hydrogen and 30 mL / min argon to obtain the reduced catalyst (BaCo). 0.1 Pb 0.9 O3) 还原态 .
[0168] Example 2
[0169] The method for preparing the self-healing catalyst in this embodiment includes the following steps:
[0170] (1) Weigh equal amounts (5 mmol) of three triblock copolymers, P121, P123 and F127, using an analytical balance. Dissolve the three substances in 200 mL of 1 mol / L hydrochloric acid solution and stir in a 30 °C water bath until completely dissolved to obtain a mixture.
[0171] (2) 30 mL of tetraethyl orthosilicate (TEOS) was slowly added to the mixture obtained in step (1), and stirred at 400 r / min for 10 h in a 30 °C water bath. The resulting milky white mixture was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and placed in an oven for hydrothermal synthesis at 120 °C for 24 h. The polytetrafluoroethylene-lined hydrothermal reactor was removed, cooled to room temperature, the sample was filtered, dried at 100 °C, and then transferred to a muffle furnace and calcined at 550 °C for 4 h to obtain a hard film agent.
[0172] (3) Weigh 0.607g (1.6mmol) Pb(CH3CO2)2·3H2O, 0.510g (2mmol) Ba(CH3CO2) and 0.116g (0.4mmol) Co(NO3)26H2O, transfer them into 200mL of deionized water, and add 0.15-0.2mL (e.g., 0.2mL) of concentrated nitric acid to inhibit the hydrolysis of the metal salts and obtain a composite solution.
[0173] (4) Weigh 5g of the hard film agent obtained in step (2) and 0.5g of citric acid and add them to the composite solution obtained in step (3). After stirring and mixing, transfer the mixture to a rotary evaporator and evaporate it to dryness to obtain the precipitate.
[0174] (5) After drying the precipitate obtained in step (4), it was calcined in a muffle furnace at 950°C for 4 hours. After calcination, the sample was washed in 100 mL of 30 wt% sodium hydroxide solution at 40°C for 4 hours to obtain the oxidized catalyst (BaCo). 0.2 Pb 0.8 O3) 氧化态 .
[0175] (6) Take the (BaCo) obtained in step (5) 0.2Pb 0.8 O3) 氧化态 The catalyst was transferred to a tubular furnace and reduced at 600°C for 4 hours in a mixed gas atmosphere of 10 mL / min hydrogen and 30 mL / min argon to obtain the reduced catalyst (BaCo). 0.2 Pb 0.8 O3) 还原态 .
[0176] Example 3
[0177] The method for preparing the self-healing catalyst in this embodiment includes the following steps:
[0178] (1) Weigh equal amounts (5 mmol) of three triblock copolymers, P121, P123 and F127, using an analytical balance. Dissolve the three substances in 200 mL of 1 mol / L hydrochloric acid solution and stir in a 30 °C water bath until completely dissolved to obtain a mixture.
[0179] (2) 30 mL of tetraethyl orthosilicate (TEOS) was slowly added to the mixture obtained in step (1), and stirred at 400 r / min for 10 h in a 30 °C water bath. The resulting milky white mixture was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and placed in an oven for hydrothermal synthesis at 120 °C for 24 h. The polytetrafluoroethylene-lined hydrothermal reactor was removed, cooled to room temperature, the sample was filtered, dried at 100 °C, and then transferred to a muffle furnace and calcined at 550 °C for 4 h to obtain a hard template agent.
[0180] (3) Weigh 0.531g (1.4mmol) Pb(CH3CO2)2·3H2O, 0.510g (2mmol) Ba(CH3CO2) and 0.174g (0.6mmol) Co(NO3)26H2O, transfer them into 200mL of deionized water, and add 0.15-0.2mL (e.g., 0.2mL) of concentrated nitric acid to inhibit the hydrolysis of the metal salts and obtain a composite solution.
[0181] (4) Weigh 5g of the hard film agent obtained in step (2) and 0.5g of citric acid and add them to the composite solution obtained in step (3). After stirring and mixing, transfer the mixture to a rotary evaporator and evaporate it to dryness to obtain the precipitate.
[0182] (5) After drying the precipitate obtained in step (4), it was calcined in a muffle furnace at 950°C for 4 hours. After calcination, the sample was washed in 100 mL of 30 wt% sodium hydroxide solution at 40°C for 4 hours to obtain the oxidized catalyst (BaCo). 0.3 Pb 0.7 O3) 氧化态 .
[0183] (6) Take the (BaCo) obtained in step (5) 0.3 Pb 0.7 O3) 氧化态 The catalyst was transferred to a tubular furnace and reduced at 600°C for 4 hours in a mixed gas atmosphere of 10 mL / min hydrogen and 30 mL / min argon to obtain the reduced catalyst (BaCo). 0.3 Pb 0.7 O3) 还原态 .
[0184] Example 4
[0185] The method for preparing the self-healing catalyst in this embodiment includes the following steps:
[0186] (1) Weigh equal amounts (5 mmol) of three triblock copolymers, P121, P123 and F127, using an analytical balance. Dissolve the three substances in 200 mL of 1 mol / L hydrochloric acid solution and stir in a 30 °C water bath until completely dissolved to obtain a mixture.
[0187] (2) 30 mL of tetraethyl orthosilicate (TEOS) was slowly added to the mixture obtained in step (1), and stirred at 400 r / min for 10 h in a 30 °C water bath. The resulting milky white mixture was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and placed in an oven for hydrothermal synthesis at 120 °C for 24 h. The polytetrafluoroethylene-lined hydrothermal reactor was removed, cooled to room temperature, the sample was filtered, dried at 100 °C, and then transferred to a muffle furnace and calcined at 550 °C for 4 h to obtain a hard film agent.
[0188] (3) Weigh 0.455g (1.2mmol) Pb(CH3CO2)2·3H2O, 0.510g (2mmol) Ba(CH3CO2) and 0.233g (0.8mmol) Co(NO3)26H2O, transfer them into 200mL of deionized water, and add 0.15-0.2mL (e.g., 0.2mL) of concentrated nitric acid to inhibit the hydrolysis of the metal salts and obtain a composite solution.
[0189] (4) Weigh 5g of the hard film agent obtained in step (2) and 0.5g of citric acid and add them to the composite solution obtained in step (3). After stirring and mixing, transfer the mixture to a rotary evaporator and evaporate it to dryness to obtain the precipitate.
[0190] (5) After drying the precipitate obtained in step (4), it was calcined in a muffle furnace at 950°C for 4 hours. After calcination, the sample was washed in 100 mL of 30 wt% sodium hydroxide solution at 40°C for 4 hours to obtain the oxidized catalyst (BaCo). 0.4 Pb 0.6 O3)氧化态 .
[0191] (6) Take the (BaCo) obtained in step (5) 0.4 Pb 0.6 O3) 氧化态 The catalyst was transferred to a tubular furnace and reduced at 600°C for 4 hours in a mixed gas atmosphere of 10 mL / min hydrogen and 30 mL / min argon to obtain the reduced catalyst (BaCo). 0.4 Pb 0.6 O3) 还原态 .
[0192] Example 5 (BaCo) x Pb (1-x) (Case where x = 0)
[0193] This embodiment is basically the same as embodiment 1, except that:
[0194] The catalyst does not contain Co, therefore the preparation method is as follows:
[0195] Step (3) is as follows: Weigh 0.759 g (2 mmol) Pb(CH3CO2)2·3H2O and 0.510 g (2 mmol) Ba(CH3CO2), transfer them into 200 mL of deionized water, and add (for example, 0.2 mL) concentrated nitric acid to inhibit the hydrolysis of the metal salt and obtain a composite solution.
[0196] Step (5) yields an oxidized catalyst (BaPbO3). 氧化态 ;
[0197] Step (6) yields a reduced catalyst (BaPbO3). 还原态。
[0198] Example 6 (Lower limit of hydrothermal synthesis temperature)
[0199] This embodiment is basically the same as embodiment 1, except that:
[0200] In step (2), the temperature of the hydrothermal synthesis reaction is 80℃.
[0201] Example 7 (Upper Limit of Hydrothermal Synthesis Temperature)
[0202] This embodiment is basically the same as embodiment 1, except that:
[0203] In step (2), the temperature of the hydrothermal synthesis reaction is 150℃.
[0204] Example 8 (lower limit of calcination temperature)
[0205] This embodiment is basically the same as embodiment 1, except that:
[0206] In step (2), the roasting temperature is 400℃.
[0207] Example 9 (Upper Limit of Calcination Temperature)
[0208] This embodiment is basically the same as embodiment 1, except that:
[0209] In step (2), the roasting temperature is 800℃.
[0210] Example 10 (Lower limit of calcination temperature)
[0211] This embodiment is basically the same as embodiment 1, except that:
[0212] In step (5), the calcination temperature is 800℃.
[0213] Example 11 (Upper Limit of Calcination Temperature)
[0214] This embodiment is basically the same as embodiment 1, except that:
[0215] In step (5), the calcination temperature is 1100℃.
[0216] Example 12 (Lower Limit of Reduction Temperature)
[0217] This embodiment is basically the same as embodiment 1, except that:
[0218] In step (6), the reduction temperature is 400℃.
[0219] Example 13 (Upper Limit of Reduction Temperature)
[0220] This embodiment is basically the same as embodiment 1, except that:
[0221] In step (6), the reduction temperature is 1000℃.
[0222] Comparative Example 1
[0223] The catalyst used in this comparative example was a Co2O3 / Al2O3 catalyst purchased from a company in Shanghai, with a Co loading of 5 wt%.
[0224] Comparative Example 2
[0225] The catalyst used in this comparative example was a MnO2 / Al2O3 catalyst purchased from a company in Beijing, with a manganese loading of 7 wt%.
[0226] II. Catalyst Application
[0227] Application Example 1
[0228] 20 mL of the catalyst prepared in Example 1 (40-60 mesh) was added to a fixed bed. The tail gas from the isobutyric anhydride cracking reaction was used as the probe gas at a flow rate of 200 mL / min. The cracking tail gas was a simulated gas containing 40% CO by volume, with the remainder being 50% nitrogen and 10% oxygen. The reaction space velocity was 4500 h⁻¹. -1 The volume of oxygen used was 21% of the volume of the tail gas from the isobutyric anhydride cracking reaction (i.e., the oxygen concentration was 21%). The reaction was held for 30 minutes at each of the following temperatures: 150℃, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃, 550℃ and 600℃.
[0229] Application Example 2
[0230] This application example is basically the same as Application Example 1, except that:
[0231] The catalyst is the catalyst prepared in Example 2.
[0232] Application Example 3
[0233] This application example is basically the same as Application Example 1, except that:
[0234] The catalyst is the catalyst prepared in Example 3.
[0235] Application Example 4
[0236] This application example is basically the same as application example 1, except that the catalyst is the catalyst prepared in example 4.
[0237] Application Example 5
[0238] This application example is basically the same as application example 1, except that the catalyst is the catalyst prepared in example 5.
[0239] Application Example 6 (Lower Hourly Space Limit)
[0240] This application example is basically the same as Application Example 1, except that:
[0241] The reaction space velocity is 4000 h⁻¹ -1 .
[0242] Application Example 7 (Upper Limit of Reaction Space Velocity)
[0243] This application example is basically the same as Application Example 1, except that:
[0244] The reaction space velocity is 5000 h⁻¹ -1 .
[0245] Application Example 8 (Lower Limit of Oxygen Concentration)
[0246] This application example is basically the same as application example 1, except that the volume of oxygen used is 10% of the volume of the tail gas from the isobutyric anhydride cracking reaction.
[0247] Application Example 9 (Upper Limit of Oxygen Concentration)
[0248] This application example is basically the same as application example 1, except that the volume of oxygen used is 40% of the volume of the tail gas from the isobutyric anhydride cracking reaction.
[0249] Comparative Application Example 1
[0250] This application example is basically the same as Comparative Application Example 1, except that the catalyst is the same as that in Comparative Example 1.
[0251] Comparative Application Example 2
[0252] This application example is basically the same as Comparative Application Example 1, except that the catalyst is the catalyst of Comparative Example 2.
[0253] III. Catalyst Characterization and Catalyst Reaction Effect
[0254] 1. Catalyst Characterization
[0255] The catalysts prepared in each example and comparative example were subjected to X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) tests.
[0256] Figure 1 Comparison of X-ray diffraction (XRD) test results for the catalysts prepared in Examples 1-4. From... Figure 1 It can be seen that the barium leadate catalyst was successfully synthesized.
[0257] Figure 2 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the catalyst prepared in Example 1. Figure 2 As can be seen, the full XPS spectrum in Figure a shows BaCo 0.1 Pb 0.9 The peaks of Ba 3d, Co 2p, Pb 4f, C 1s, and O 1s in O3. As shown in Figure b, the high-resolution spectrum of Pb 4f can be deconvoluted into two characteristic peaks, attributed to Pb 4f7 / 2 and Pb 4f5 / 2, respectively. In Figure c, the doublet peaks of Co 3d3 / 2 are 780 eV and 795 eV, respectively. In Figure d, the doublet peaks of Ba 3d3 / 2 are 794 eV and 796 eV, and the doublet peaks of Ba 3d5 / 2 are 779 eV and 781 eV.
[0258] 2. Effect of catalyst reaction
[0259] The conversion rate of CO in the tail gas of each application example and application comparison was tested.
[0260] Figure 3 The reaction effect diagrams are for the catalysts prepared in Examples 1-4 and Comparative Examples 1-2 (i.e., reaction effect diagrams for Application Examples 1-4 and Comparative Application Examples 1-2). From Figure 3 It can be seen that the embodiments are significantly better than the comparative examples.
[0261] Figure 4 This is a lifetime evaluation graph for the catalyst prepared in Example 4. From... Figure 4 It can be seen that the catalyst exhibits excellent reaction stability, and once deactivated, it can be regenerated using a simple method. The regeneration method involves sequentially subjecting the deactivated catalyst to oxidation and reduction treatments. The oxidation treatment is carried out in an air atmosphere at a heat treatment temperature of 800℃ for 4 hours. Then, the oxidized catalyst is placed in a reducing atmosphere at 700℃ for 3 hours to obtain the regenerated catalyst, which is then used to continue the reaction. The hydrogen atmosphere is a mixture of hydrogen and nitrogen, with hydrogen comprising 10% by volume.
[0262] In this application, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0263] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0264] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A catalyst with self-healing properties, characterized in that, The catalyst comprises at least one of the compounds shown in Formula I; BaCo x Pb (1-x) O3 Formula I, Where x takes values from 0.2 to 0.3; The compound represented by Formula I has a perovskite structure.
2. A method for preparing a catalyst with self-healing properties as described in claim 1, characterized in that, include: The catalyst with self-healing properties was prepared using a nano-casting method.
3. The preparation method according to claim 2, characterized in that, The preparation of the self-healing catalyst using the nanocasting method includes: The template agent and silicon source are subjected to a hydrothermal synthesis reaction, followed by a first calcination to obtain a hard template agent; The hard template agent, the composite solution containing M source, and the additives were mixed and then subjected to rotary evaporation to obtain a precipitate; The precipitate was dried, then calcined and washed to obtain the oxidized catalyst with self-healing properties. The catalyst with self-healing properties in the oxidized state is subjected to a first heat treatment under a first reducing atmosphere to obtain the catalyst with self-healing properties. In the composite solution containing source M, M is Ba, Co, and Pb.
4. The preparation method according to claim 3, characterized in that, The template agent includes at least one of triblock copolymer P121, triblock copolymer P123, and triblock copolymer F127; And / or, the silicon source includes at least one of tetraethyl orthosilicate, tetramethyl orthosilicate, and tetrapropoxysilane; And / or, the mass ratio of the template agent to the silicon source is (1-5):(50-500); And / or, the temperature of the hydrothermal synthesis reaction is 80-150℃, and the time of the hydrothermal synthesis reaction is 12-24h; And / or, the temperature of the first calcination is 400-800℃, and the time of the first calcination is 2-4h.
5. The preparation method according to claim 4, characterized in that, The template agent is a mixture of triblock copolymer P121, triblock copolymer P123, and triblock copolymer F127 in a molar ratio of 1:1:1; And / or, the silicon source is tetraethyl orthosilicate; And / or, the temperature of the hydrothermal synthesis reaction is 90-110°C; And / or, the temperature of the first calcination is 550-700℃.
6. The preparation method according to claim 3, characterized in that, In the composite solution containing source M, the molar concentration of Ba source is 10 mmol / L, the molar concentration of Co source is 2-3 mmol / L, the molar concentration of Pb source is 7-8 mmol / L, and the total molar concentration of Co source and Pb source is 10 mmol / L. And / or, in the composite solution containing source M, the solvent includes water; And / or, the adjuvant includes at least one of citric acid, oxalic acid, and myristic acid; And / or, the calcination temperature is 800-1100℃, and the calcination time is 3-6h; And / or, the detergent used for washing includes an alkaline solution, which includes at least one of a 10-40 wt% sodium hydroxide solution, a 10-40 wt% potassium hydroxide solution, or a 10-40 wt% mixed solution of sodium hydroxide and potassium hydroxide; And / or, the first reducing atmosphere includes hydrogen; And / or, the temperature of the first heat treatment is 400-1000℃, and the time of the first heat treatment is 1-6h.
7. The preparation method according to claim 6, characterized in that, The mass ratio of the hard template agent, the M source, and the auxiliary agent is (1-5):(0.5-10):(0.1-0.5). And / or, the adjuvant is citric acid; And / or, the calcination temperature is 950-1000℃, and the calcination time is 4-5h; And / or, the reducing atmosphere is a mixture of hydrogen and an inert gas, wherein the hydrogen flow rate is 5-25 mL / min and the argon flow rate is 15-75 mL / min; And / or, the temperature of the first heat treatment is 400-800℃, and the time of the first heat treatment is 2-4h.
8. The application of the self-healing catalyst as described in claim 1 or the self-healing catalyst prepared by the preparation method of any one of claims 2 to 7 in tail gas treatment; wherein the tail gas is isobutyric anhydride cracking tail gas.
9. A method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas, characterized in that, include: The isobutyric anhydride cracking tail gas is treated by catalytic oxidation using a catalyst, wherein the catalyst is the self-healing catalyst as described in claim 1 or the self-healing catalyst prepared by the preparation method of any one of claims 2 to 7.
10. The method according to claim 9, characterized in that, The conditions for treating isobutyric anhydride cracking tail gas using catalyst oxidation include: a reaction temperature of 250-500℃ and a reaction space velocity of 4000-5000 h⁻¹. -1 The volume of oxygen used is 10-40% of the volume of isobutyric anhydride cracking tail gas.
11. The method according to claim 9, characterized in that, The method for catalytic oxidation treatment of isobutyric anhydride cracking tail gas further includes: When the catalyst is deactivated, it is restored to activity through pretreatment to obtain a regenerated catalyst; The pretreatment method includes: sequentially oxidizing and reducing the deactivated catalyst.
12. The method according to claim 11, characterized in that, The oxidation process is carried out in an oxygen-containing atmosphere.
13. The method according to claim 12, characterized in that, The oxidation treatment method includes: calcining the deactivated catalyst in an oxygen-containing atmosphere at 400-800°C for 2-4 hours.
14. The method according to claim 11, characterized in that, The reduction process is carried out in a second reducing atmosphere, which includes hydrogen.
15. The method according to claim 14, characterized in that, The reduction treatment method includes: subjecting the deactivated catalyst, which has undergone the oxidation treatment, to a second heat treatment at 400-800°C for 2-4 hours in a second reducing atmosphere.
Citation Information
Patent Citations
Catalyst as well as preparation method and application thereof
CN119281320A